Does talent exist? Yes! - Simonton, D. K. (Routledge handbook of talent identification and development in sport, 2017)
The scientific study of talent is frequendy said to begin with Francis Galton`s 1869 Hereditary Genius: A n Inquiry into Its Laws and Consequences (Simonton, 2003). Yet it might be more accurate to say that the explicit study of talent began with an article that he published four years earlier (Galton, 1865). The latter explicidy used the expression "hereditary talent" in place of "hereditary genius." Nonetheless, at this time Galton used talent and genius more or less interchangeably. In addition, the 1865 article can be considered a pilot study for the book-length treatment published in 1869. The latter not only could devote more space to elaborating his theoretical ideas, but also could contain more extensive space to an empirical documentation of those ideas. More specifically, Galton dedicated himself to proving that genius or talent was a very real phenomenon: Eminent achievement in a diversity of domains could be attributed to inherited abilities. This conclusion was demonstrated for achievement domains as varied as politics, religion, law, war, science, literature, painting, music, and sports. In each case, Galton used the family pedigree method— which he was the first to apply in scientific research— to establish that eminent achievers were related to other eminent achievers at incidence rates that far exceeded the population baselines. Genius (or talent) was born, not made.